The association between composite inflammatory indicators and the clinicopathological characteristics of differentiated thyroid carcinoma - Yang, Li-Yuan; Yang, Li-Peng (Frontiers in Molecular Biosciences, 2025)
PurposeThis study examined the associations between composite inflammatory indicators—including the Monocyte-to-Lymphocyte Ratio (MLR), Systemic Inflammation Response Index (SIRI), and Systemic Immune-Inflammation Index (SII)—and the clinicopathological characteristics in patients with Differentiated Thyroid Carcinoma (DTC). To provide a novel insight into refining patient selection criteria for active surveillance (AS) strategies in DTC patients.MethodsThis retrospective study analyzed preoperative MLR, SIRI, and SII values in 231 DTC patients treated at Shanghai Sixth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine between January 2021 and February 2023. Comparisons of these inflammatory indicators were performed across subgroups stratified by clinicopathological characteristics. Subsequently, patients were categorized into low-expression and high-expression groups based on the median values of MLR, SIRI, and SII, followed by comparative analyses of clinicopathological features between the two groups.ResultsComparative Analysis: SIRI levels were significantly elevated (P < 0.05) in patients with larger maximum tumor diameter, higher Ki-67 index, lymph node metastasis (LNM), capsular invasion and bilateral thyroid tumors. Similarly, SII levels were significantly elevated (P < 0.05) in patients with larger maximum tumor diameter, aggressive pathologic variants, LNM, and capsular invasion. In contrast, the MLR showed no significant associations with any of the clinicopathological subgroups analyzed (all P > 0.05). Subgroup Analysis: Compared to the high-MLR group, the low-MLR group showed a significantly lower prevalence of psammoma bodies, and lower incidence of multifocal tumors (all P < 0.05). SIRI Group Comparisons: The high-SIRI group exhibited significantly larger maximum tumor diameter, higher rates of lymphovascular invasion compared to those in the low-SIRI group (P < 0.05). SII Group Comparisons: The high-SII group demonstrated a significantly higher prevalence of aggressive pathologic variants compared to the low-SII group (P < 0.05).ConclusionPatients with DTC presenting elevated preoperative levels of MLR, SIRI, and SII demonstrated a significantly higher incidence of multiple adverse clinicopathological features postoperatively compared to those with lower baseline inflammatory indicators levels. These findings suggest that MLR, SIRI, and SII may serve as predictive biomarkers for adverse tumor clinicopathological characteristics in DTC.